Beginning Drupal 7 - Tomlinson, Todd (Apress, 2012)
In its relatively short life, Drupal has had a tremendous impact on the landscape of the Internet. As a web content management system (CMS), Drupal has enabled the creation of feature- and content-rich websites for organizations large and small. As a web application framework, Drupal is changing the way that people think about web application development. When I experienced the power of the Drupal platform for the first time, I knew that it was something more than just another content management solution. When I saw how easily and quickly I could build feature-rich websites, I shifted gears and focused my entire career around Drupal. While working with clients, I was often asked, “Where can I go to find information for someone who is new to Drupal?” Unfortunately there wasn’t a comprehensive resource that I could point them to, and thus began my journey of writing this book. I’m also often asked, “What is Drupal?” The short answer is, “Drupal is an open source web content management system that allows you to quickly and easily create simple to complex sites that span everything from a simple blog, a corporate site, a social networking site, or virtually anything you can dream up.” What you can build with Drupal is only limited by your imagination and the time you have to spend with the platform.